Whatever Gets you Through the Night: Officer Coping Strategies after the High-Profile Line of Duty Deaths in Dallas and Baton Rouge - Clifton, Stacey (American journal of criminal justice, 2018)
The policing profession has recently experienced events that affected officers across the nation. Several high-profile cases involving police and members of minority communities intensified the tensions among these groups. Amid public criticisms of policing, law enforcement officers have become targets of attacks. Multiple cases of officer ambushes and assassinations have further troubled the already stressful occupational position of law enforcement. This study investigates what coping strategies officers used after the deadly attacks on police in Dallas, Texas and Baton Rouge, Louisiana that occurred in July, 2016. We also investigate how the coping strategies used affects job motivation among officers. Our findings suggest officers turned to three coping strategies: support networks, stoic self-help, and self-medication. These coping strategies were found to be ineffective mechanisms for protecting officer job motivation; however, some strategies adversely affected motivation more than others. Understanding how officers are coping and why effective strategies are not being employed adequately is imperative for both the safety of officers and the public.